Osteomyelitis associated with Actinomyces sp. in the mandibular bone: case report (Research, Society and Development, 2020)
The Actinomycosis is a rare infection caused by microorganisms of the genus Actinomyces. Its clinical presentation may resemble or mask other infectious processes, which makes the diagnosis complex and compromises therapeutic success. The aim of this work is to report a case of osteomyelitis caused by a bacterial infection, discuss the clinical manifestations, forms of diagnosis and treatment. This is a descriptive, retrospective and qualitative study, carried out using the direct observation technique. Male patient, leucoderma, 65 years old, attended on maxillofacial surgery ambulatory with pain complaint in anterior region of the mandible and history of extraction 5 months ago on region with episodes of drainage of purulent secretion. Physical examination revealed absence of tooth 31 and intact tissues, and radiographic examination was requested, where was observed bone sequestration in the region of alveolar bone, with hypothesis of osteomyelitis. Surgical treatment was recommended  with excision of the radiopaque area, associated with antibiotic therapy. Histopathological evaluation confirmed the infectious process associated with colonies of bacteria Actinomyces sp.; the patient progressed well with complete remission of the infectious process. Thus, histopathological confirmation is an important tool for the rapid diagnosis and establishment of effective treatment, considering that actinomycosis makes a differential diagnosis with several diseases and has high local destructive power.